Ruin Probabilities in Generalized Risk Process with a Marko Chain Interest Model - Hien, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 29 No 1, 2013)
Abstract: This paper deals with ruin probabilities in generalized discrete time risk process with Markov chain interest model. After, recursive and integral equations for the ruin probabilities are given. When interest rates can be negative and loss distribution have regularly varying tails, the paper built an asymptotic formula for the finite time ruin probability by an inductive approach on the recursive equations. Keywords : Discrete time risk model; Time of ruin; Ruin probability; Recursive eqution; Rate of interest.